Changes in type 1 diabetes health indicators from high school to college. Issue 2 (17th February 2016) - Monaghan, Maureen; King, Megan McCormick; Alvarez, Vanessa; Cogen, Fran R.; Wang, Jichuan
ABSTRACT: Objective : Evaluate trajectories of type 1 diabetes health indicators from high school through the first year of college.Participants : Seventy-four students with type 1 diabetes who maintained pediatric endocrinology care during the first year of college.Methods : Hemoglobin A1c (HbA1c), blood glucose monitoring frequency, body mass index (BMI), and clinic attendance data were collected via retrospective medical chart review in spring 2012. Group-based trajectory models evaluated diabetes-related health indicators over time and identified distinct growth trajectory groups.Results : BMI increased and clinic attendance decreased in the first year of college. Trajectories for other health indicators were heterogeneous and stable over time; 69% of students were classified as having stable good glycemic control. Racial minority youth and youth on conventional insulin regimens were disproportionally represented in higher-risk groups.Conclusions : Diabetes health indicators are stable or decline upon college entrance. Results signal the need for targeted support for college students with type 1 diabetes.